Baku. Uwagi na marginesie Przedwiośnia (i jego recepcji) - Morawiec, Arkadiusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article concerns Stefan Żeromski’s Przedwiośnie, one of the most important Polish novels of the twentieth century. So far the work was considered, especially its first part (Szklane domy), whose plot is set in Baku, mainly in the context of the Bolshevik Revolution. It was ignored, however, that the historical background of the novel (its plot) are also other, linked with that revolution (and partly caused by the Bolsheviks), dramatic historical events: ethnic feuds between Armenians and Azeris (“Tartars”) and the Turkish intervention, which is one of the stages of the Armenian Genocide. The fate of Cezary Baryka, the main character of Przedwiośnie, is usually seen in terms of transformation, education, ideological development. It is worth noting that the Baku massacres are for Cezary not only a lesson or a warning, but they are also the source of his demoralization; it can be concluded that the hero is “infected with death”.